1999
DOI: 10.1038/sj.bjc.6690388
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal gains and losses in primary colorectal carcinomas detected by CGH and their associations with tumour DNA ploidy, genotypes and phenotypes

Abstract: SummaryComparative genomic hybridization (CGH) is used to detect amplified and/or deleted chromosomal regions in tumours by mapping their locations on normal metaphase chromosomes. Forty-five sporadic colorectal carcinomas were screened for chromosomal aberrations using direct CGH. The median number of chromosomal aberrations per tumour was 7.0 (range 0-19). Gains of 20q (67%) and losses of 18q (49%) were the most frequent aberrations. Other recurrent gains of 5p, 6p, 7, 8q, 13q, 17q, 19, X and losses of 1p, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
143
5
2

Year Published

2000
2000
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(172 citation statements)
references
References 53 publications
22
143
5
2
Order By: Relevance
“…3,4,17 The reason for such an association remains to be discovered. However, we and De Angelis et al 13 found an inverse relationship between chromosome 4 loss and reduced apoptosis.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…3,4,17 The reason for such an association remains to be discovered. However, we and De Angelis et al 13 found an inverse relationship between chromosome 4 loss and reduced apoptosis.…”
Section: Discussioncontrasting
confidence: 53%
“…4,[18][19][20] Loss of chromosome arm 9p is not an infrequent event in colorectal cancer. 13,21 We identified a significant association between 9p loss and high Bold represents values which are statistically significant.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…[21][22][23][24] CGH studies on both colorectal adenomas and carcinomas have also confirmed the gain of chromosome 7 material as a frequent change. 11,12,25,26 Ried et al 12 demonstrated gain of chromosome 7 material in 4 of 12 in what they described as high-grade adenomas. The neoplasia-specificity of ϩ7 has been questioned, however, both in the context of colorectal carcinogenesis and in general.…”
Section: Discussionmentioning
confidence: 99%
“…5-7,16 -18 Similar results have been obtained by CGH analyses of colorectal adenomas and carcinomas. 11,25,26 In adenomas, Ried et al 12 described gain of chromosome 13 material in 1 of 26 adenomas and gain of chromosome 20 material in 3 of 26 adenomas. All cases with these changes were described as high-grade adenomas.…”
Section: Discussionmentioning
confidence: 99%